A novel embeddable spherical smart aggregate for structural health monitoring: part II. Numerical and experimental verifications. (22nd August 2017) - Kong, Qingzhao; Fan, Shuli; Mo, Y L; Song, Gangbing
Abstract: The newly developed spherical smart aggregate (SSA) based on a radially polarized spherical piezoceramic shell element has unique omnidirectional actuating and sensing capabilities that can greatly improve the detection aperture and provide additional functionalities in health monitoring applications in concrete structures. Detailed fabrication procedures and electrical characterization of the SSA have been previously studied (Part I). In this second paper (Part II), the functionalities of the SSA used in both active sensing and passive sensing approaches were investigated in experiments and numerical simulations. One SSA sample was embedded in a 1 ft 3 concrete specimen. In the active sensing approach, the SSA was first utilized as an actuator to generate stress waves and six conventional smart aggregates (SA) mounted on the six faces of the concrete cube were utilized as sensors to detect the wave response. Conversely, the embedded SSA was then utilized as a sensor to successively detect the wave response from each SA. The experimentally obtained behavior of the SSA was then compared with the numerical simulation results. Further, a series of impact tests were conducted to verify the performance of the SSA in the detection of the impact events from different directions. Comparison with the wave response associated with different faces of the cube verified the omnidirectional actuating and sensing capabilities of the SSA.